Neural network involving medial orbitofrontal cortex and dorsal periaqueductal gray regulation in human alcohol abuse - Jia, Tianye; Xie, Chao; Banaschewski, Tobias; Barker, Gareth J.; Bokde, Arun L. W.; Büchel, Christian; Quinlan, Erin Burke; Desrivières, Sylvane; Flor, Herta; Grigis, Antoine; Garavan, Hugh; Gowland, Penny; et al. (Science advances, 2021)
Prompted by recent evidence of neural circuitry in rodent models, functional magnetic resonance imaging and functional connectivity analyses were conducted for a large adolescent population at two ages, together with alcohol abuse measures, to characterize a neural network that may underlie the onset of alcoholism. A network centered on the medial orbitofrontal cortex (mOFC), as well as including the dorsal periaqueductal gray (dPAG), central nucleus of the amygdala, and nucleus accumbens, was identified, consistent with the rodent models, with evidence of both inhibitory and excitatory coregulation by the mOFC over the dPAG. Furthermore, significant relationships were detected between raised baseline excitatory coregulation in this network and impulsivity measures, supporting a role for negative urgency in alcohol dependence. - Neuroimaging data from 1890 adolescents implicated an orbitofronto-amygdalo-periaqueductal gray network in early alcohol abuse. - Neuroimaging data from 1890 adolescents implicated an orbitofronto-amygdalo-periaqueductal gray network in early alcohol abuse.
Gesehen am 19.04.2021